Training and Incentives on Knowledge Sharing: The Role of Trust - Syafira Anggraini; Muhammad Ali Fikri; Poppy Laksita Rini; Made Galih Wisnu Wardana (Universitas Diponegoro, 2025)
A crucial component of knowledge management that supports creativity, efficiency, and organizational sustainability is information sharing. The use of incentives and training in promoting knowledge-sharing among staff members. elements that affect how well incentives and training work to foster a culture of knowledge sharing. The purpose of this study is to ascertain how incentives and training affect knowledge sharing. PT. Kereta Api Indonesia (KAI) Operation Area 6 in Yogyakarta served as the study's research site. Quantitative research is used in this study. Primary data sources were employed in this study. A questionnaire was employed as a method of gathering data for this investigation. PT. KAI Operating Area 6 Yogyakarta provided a total of 88 respondents for this study's census sample strategy. The data analysis technique used is bootstrapping with Smart PLS version 4. The research results demonstrated that trust has a favourable impact on knowledge sharing, as do training variables and training itself. Furthermore, the findings demonstrate that trust and training improve worker performance. Knowledge sharing is not positively impacted by incentive variables, but trust is positively impacted by incentives, and knowledge sharing is positively impacted by both trust and incentives. The research's implication is to enhance employee performance by offering pertinent insight into the connection between trust and information sharing.